2013
DOI: 10.3892/mco.2013.188
|View full text |Cite
|
Sign up to set email alerts
|

Esophagitis resulting from treatment with crizotinib for anaplastic lymphoma kinase rearrangement-positive lung adenocarcinoma: A case report

Abstract: Abstract. Non-small-cell lung cancer (NSCLC) is the most commonly diagnosed type of cancer and is a leading cause of cancer-related mortality worldwide. Treatment is currently focused on individualization according to the molecular profile of the disease. Here we present the case of a 41-year-old patient who presented with multiple pulmonary nodules, a left pleural effusion and an ovarian tumor. Adenocarcinoma of the lung was diagnosed from pathological examination of the pleural effusion and the surgically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The major adverse effects of crizotinib are vision disorder, diarrhea, nausea, and vomiting. In addition, several reports have demonstrated that severe esophagitis may be induced by crizotinib (8)(9)(10)(11)(12)(13). Here, we report a case of recurrent esophagitis induced by crizotinib that was successfully managed by the alternate-day administration of crizotinib.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The major adverse effects of crizotinib are vision disorder, diarrhea, nausea, and vomiting. In addition, several reports have demonstrated that severe esophagitis may be induced by crizotinib (8)(9)(10)(11)(12)(13). Here, we report a case of recurrent esophagitis induced by crizotinib that was successfully managed by the alternate-day administration of crizotinib.…”
Section: Introductionmentioning
confidence: 82%
“…To our knowledge, there are six case reports of crizotinib-induced esophagitis (8)(9)(10)(11)(12)(13). The mechanism of crizotinib-induced esophagitis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been some previous case reports of the efficacy of ALK -tyrosine kinase inhibitor (TKI) therapy in patients in whom ALK protein expression was detected in MPE samples (31,32), we obtained efficacy data with crizotinib in a total of 11 lung adenocarcinoma patients who were Ventana IHC ALK (D5F3)-positive. Two patients had CR (2/11, 18.2%), 5 had PR (5/11, 45.5%), and 3 had SD (3/11, 27.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Since its approval, there have been five cases of esophagitis reported in patients taking crizotinib, which have been attributed to “pill esophagitis” in two cases and unknown causes in the other three cases . In three of these cases, crizotinib was not recommenced or was recommenced, and maintained, at a lower dose.…”
Section: Discussionmentioning
confidence: 99%